2012
DOI: 10.1002/hlca.201100286
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three New Flavonoids from the Peels of Citrus unshiu

Abstract: Three new flavonoids, 5,6,7,8,3′,4′‐hexamethoxyhomoflavone (1), 5,6,7,8,4′‐pentamethoxyhomoflavone (2) and 3,6,7,8,2′,5′‐hexamethoxyflavone (3) were isolated from the peels of mature fruits of Citrus unshiu Marcow (Rutaceae), together with the three known compounds 6,7,8,4′‐tetramethoxyflavone (=6,7,8‐trimethoxy‐2‐(4‐methoxyphenyl)‐4H‐1‐benzopyran‐4‐one), 3,5,7,8,2′,5′‐hexamethoxyflavone (=2‐(2,5‐dimethoxyphenyl)‐3,5,7,8‐tetramethoxy‐4H‐1‐benzopyran‐4‐one), and scopoletin (=7‐hydroxy‐6‐methoxy‐2H‐1‐benzopyran‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…. All NMR spectra (1D and 2D NMR), and mass spectrometry (Table S1) were consistent with data reported for these known compounds [13,21,[30][31][32][33].…”
Section: Isolation and Structural Elucidation Of Compoundssupporting
confidence: 85%
See 1 more Smart Citation
“…. All NMR spectra (1D and 2D NMR), and mass spectrometry (Table S1) were consistent with data reported for these known compounds [13,21,[30][31][32][33].…”
Section: Isolation and Structural Elucidation Of Compoundssupporting
confidence: 85%
“…The chloroform-soluble sub-fraction of Pq was subjected to a series of open column chromatographic (CC) separations to obtain the following seven known biologically active compounds (Figure 8): 5,4′-dihydroxy-7,3′-dimethoxyflavanone (1) [18]; 5,3′,4′-trihydroxy-7methoxyflavanone (7-methoxy-eriodictyol) (2) [19]; 7-hydroxy-6-methoxy-2H-1-benzopyran-2-one, (scopoletin, 3) [20]; p-coumaroyloxytremetone (4) [13]; 5-hydroxy-7,4′,3′-trimethoxyflavanone (5); 3,5,4′-trihydroxy-7,8,3′-trimethoxyflavone (6); and 5,4′-dihydroxy-3,7,8,3′-tetramethoxyflavone (ternatin, 7) [21]. All NMR spectra (1D and 2D NMR), and mass spectrometry (Table S1) were consistent with data reported for these known compounds [13,21,[30][31][32][33]. .…”
Section: Isolation and Structural Elucidation Of Compoundssupporting
confidence: 73%
“…The peels of its fruits, called chinpi, have been used as an aromatic stomachic, cold medicine, expectorant, and antitussive [ 1 ]. Limonoids [ 2 , 3 ], flavonoids [ 4 , 5 , 6 , 7 ], tocopherol analogues [ 8 , 9 ] have been isolated from peels of C. reticulata , phenyl glycosides from flower buds [ 10 ], and a limonoid [ 11 ], flavonoids [ 11 ], and a cyclic peptide from its fruits [ 12 ]. Moreover, some bioactivities of constituents from C. reticulata have been reported, such as the suppression of adipogenesis by a limonoid [ 3 ], the inhibitory activity on histamine release from rat peritoneal mast cells [ 4 ], hypotensive activity [ 5 ] and antioxidant activity [ 6 ] of flavonoids, the radical-scavenging activity [ 8 ] and hepatoprotective and neuroprotective activities [ 9 ] of tocopherol analogues, as well as antimicrobial activities of essential oil [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Shin et al reported the isolation of three previously unreported flavonoids from the peels of mature fruits of Citrus unshiu Marcow (Rutaceae), one of which was named 3,6,7,8,2′,5′-hexamethoxyflavone (4). 12 These peels have been used in traditional Chinese medicine and some isolates from C. unshiu have been reported to exhibit antiproliferative effects. Given the interesting biological profiles of compounds 1-4 (and the diverse array of properties typically associated with flavonoids in general), we were interested in a more extensive assessment of their biological activities.…”
mentioning
confidence: 99%
“…Benzaldehyde precursor 11 was prepared from commercially available 4-hydroxybenzaldehyde (10) by MOM protection (Scheme 2). In parallel, the acetophenone building block 13 was accessed from 3,4-dimethoxyphenol (12). Claisen-Schmidt aldol condensation Attention was next turned toward the preparation of the polymethoxyflavone 4 (Scheme 4).…”
mentioning
confidence: 99%